Lack of Knowledge of the Importance of Complete Basic Immunizations - Shanti Ariandini; Kiki Novianty (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Immunization is an effort to actively generate or increase a person's immunity against disease, so that if one day he is attacked by the disease, he will only experience mild illness. Community service was carried out in Situ Udik Village about the importance of complete basic immunization because, there was still a lack of knowledge, namely, mother's knowledge about the frequency and timing of giving complete basic immunization to babies because mothers rarely read and understood the results of recording their baby's growth and development in the contents of the MCH book. Aims to determine the level of knowledge and to reduce morbidity, mortality and disability due to diseases that can be prevented by immunization in Situ Udik Village. Pre-experimental research was carried out on the community, especially the immunization targets, namely infants, toddlers, children aged 1, 2, 3. Sampling with a sampling number of 20 participants, for the results of the study used t-test analysis on pretest and post-test with p value <. 001. The results of the calculation of statistical tests using computerization, obtained a t value of 10.376 and p <.001. With this counseling, it is hoped that the community will know the importance of immunization and parents and families can find out when children need health services, especially immunization so that it does not have a negative impact on their health.